The Influence of Workload on Employee Burnout: The Moderation Role of Family Support in Indonesian Heritage Center - Syahrullah, Syahrullah; Rizaldi, Andi Risfan; Abdullah, Irwan (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The aim of this research is a) to determine the effect of workload on employee burnout at Indonesian Heritage Halls, and b) to find out whether family support can moderate by weakening or strengthening the influence of workload on employee burnout at Indonesian Heritage Halls. The type of research used in this research is quantitative using the SPSS 27 program data analysis method. The sample used in this research is 64 respondents who are employees of the Indonesian Heritage Center. The data analysis used is classical assumption testing, hypothesis testing, moderate regression analysis (MRA). The results of this research show that based on the results of data analysis, t test results and MRA test results, it was found that the workload variable had a positive and significant effect on burnout at Indonesian Heritage Centers. Meanwhile, the family support variable was unable to moderate and strengthen the influence of workload on burnout at Indonesian Heritage Centers.